Regional ecotourism sustainability assessment: research value and literature review / Li Jia Tong and Arni Abdul Gani - Tong, Li Jia; Abdul Gani, Arni (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The purpose of this paper is to study the value of ecotourism sustainability assessment, to sort out the literature review related to ecotourism sustainability assessment, and to review the current progress of international research on ecotourism sustainability assessment, etc. On this basis, it identifies the gaps in the content and methods of regional ecotourism sustainability assessment and provides a certain theoretical basis for future research in this field. It is hoped that this paper provides the needs of researchers and practitioners with some references for sustainable tourism and its definitions and applications, and also presents future research opportunities.